Exploring Students’ Continuence Intention Toward Artificial Intelligence - Sosianika, Adila; Rafdinal, Wahyu; Amalia, Fatya Alty (Jurnal Riset dan Inovasi Pembelajaran, 2024)
Various forms of Artificial intelligence (AI), including machine-driven AI, cognitive AI, and emotional AI, collaborate to provide numerous advantages in marketing research and help marketers develop effective strategies. This study applied the Technology Acceptance Model (TAM) to explore the aspects impelling students' ongoing intention to make advantages of AI in marketing research. To meet the study's objectives, this research used quantitative methods to identify AI applications in marketing research. A questionnaire survey was distributed to 200 student respondents to collect data. The collected data is examined using Importance Performance Map Analysis (IPMA). The study assesses the significance of AI in marketing research among students, revealing that attitude significantly impacts the committed to keep utilizing AI. Positive attitudes are strongly linked to continued usage, with perceived usefulness being the most critical factor, suggesting users find AI enhances their experiences. Acceptance of AI is also influenced by perceived ease of use, system, information, and service quality, as well as attitude. The results indicate that efficient system operation, improved information quality, and high-quality systems and services foster positive perceptions and preferences for AI. The results of this study offer valuable insights for educators in higher education, guiding them on effective strategies to encourage their students to utilize AI in a responsible manner, particularly within the realm of marketing research.